Evaluation of ATG5 polymorphisms in Italian patients with systemic lupus erythematosus: contribution to disease susceptibility and clinical phenotypes. (August 2018) - Ciccacci, C; Perricone, C; Alessandri, C; Latini, A; Politi, C; Delunardo, F; Pierdominici, M; Conti, F; Novelli, G; Ortona, E; Borgiani, P
Systemic lupus erythematosus (SLE) is a common heterogeneous autoimmune disease that is caused by the involvement both of genetic and environmental factors. There is evidence that autophagy is involved in several aspects of SLE pathogenesis. In particular, polymorphisms in the ATG5 gene have been observed to be associated with disease susceptibility. Our aim was to verify if ATG5 polymorphisms are involved in the susceptibility to disease and its clinical phenotypes in an Italian cohort of SLE patients. This study involved 315 SLE patients and 265 healthy controls. Three polymorphisms in the ATG5 gene (rs573775, rs6568431 and rs2245214) were investigated by allelic discrimination assay. A case-control association study, a genotype/phenotype correlation analysis and a haplotype study were performed. Moreover, an expression study was conducted in peripheral blood mononuclear cells from 15 SLE patients to verify a possible effect of the three SNPs on the expression of ATG5 . Among the three investigated SNPs, only the rs573775 SNP was significantly associated with disease susceptibility with the variant allele conferring a higher risk of developing SLE (OR = 1.50, p = 0.018 and OR = 1.48, p = 0.007 at the genotypic and allelic level, respectively). The variant allele of rs6568431 SNP was more present in patients with anemia (OR = 1.86, p = 0.009) and renal involvement (OR = 1.63, p = 0.06), while the variant allele of rs2245214 SNP was significantly associated with a higher risk of producing anti-DNA autoantibodies (OR = 1.66, p = 0.04). Carriers of the rs6568431 variant allele showed higher messenger RNA levels compared to the carriers of the wild-type allele, suggesting also a potential variant allele dose-dependent effect on gene expression. In conclusion, our study confirms a role for ATG5 polymorphisms both in disease susceptibility and in the modulation of clinical phenotypes in an Italian SLE cohort. These results further suggest that genetic variations in autophagy genes could play a role in autoimmune diseases susceptibility and are worth further investigation.